Performance Comparison of DSSCs-based Solid Electrolyte with Different Counter Electrodes - Erma Surya Yuliana; Nasikhudin Nasikhudin; Nurul Hidayat; Arif Hidayat; Nandang Mufti (Universitas Negeri Malang, 2024)
The counter electrode (CE) in dye-sensitized solar cells (DSSCs) has an essential impact on the photovoltaic performance and long-term stability of DSSCs. Carbon materials, such as activated carbon (AC) and graphene, are attractive candidates for CE materials in DSSCs due to their low cost, high thermal conductivity, and high specific surface area. In this work, the manufacture of carbon CE using the knife coating method. Then, its performance was tested using a solar simulator and electrochemical impedance spectroscopy (EIS) testing. The samples with carbon and graphene counter electrodes show efficiencies of 0.29% and 0.23%, respectively. The findings revealed that the CE-based carbon materials had a significant impact on the performance of DSSCs. The proposed carbon materials, having low-cost fabrication, high conductivity, high thermal stability, and good corrosion resistance to electrolytes, may offer a promising solution for solar cell applications.